STANDARDIZATION DIMENSION IN BUILDING an INTEGRATED DIGITAL CULTURAL HERITAGE ENVIRONMENT - BLIŪDŽIUVIENĖ, NIJOLĖ (Knygotyra, 2011)
The need for standards in the process of creating a single European information system of the cultural heritage as well as the premise for the standardized integration of Lithuanian memory institutions and the experience of such integration were the objects of the study. Cultural integration and standardized integration are presented as a conceptual basis associated with memory institutions’ participation in standardization work, finding its expression in creating the virtual information system of the cultural heritage. The concept of standardized integration, introduced by the author, generates a new cultural policy and could be considered a strategic and innovative activity by libraries, museums and archives. The documentation of projects for cultural heritage digitization and digital content management at memory institutions, initiated by the European Commission and relevant Lithuanian bodies, provide no information about the participation of project partners in standardization activities on national, European or international levels, their priorities concerning standardization work, the impact of their participation for seeking cross-sectoral agreement on the application of shared standards and the applicability of their know-how gained from participation in standardization activities within their institutions.The evaluation of standardization in the context of Lithuanian memory institutions highlights the experience and achievements against the background of the cultural and standardized integration. The substantial transformation of LST/TC 47 “Information and documentation” coincided with grand projections for cultural heritage digitization undertaken by memory institutions at the initial stages of implementing the project “Creation of the Integrated Virtual Library Information System”. The international, European and national standards, as well as other normative documents invoked in creating this information system, facilitated setting up the digital cultural heritage databank available on the Website epaveldas.lt.This innovative project was of vital importance for the national cultural policy, because significant legal acts regulating the aims, goals and methods of digitization at memory institutions participating in the creation of the integrated interaction-based system of cultural heritage had been adopted. From the viewpoint of standardization, the methodology for the interaction of archives, libraries and museums is based on a legal act dealing with the application of standards, which obliges the project partners to apply shared national standards and normative documents for the description of digital and data content, metadata coding, the preservation (archiving) of data and creation of the digital content.
Keywords: ...